Market Timing Strategies and Mutual Fund Performance - Bir, Prathamesh Pai; Mayur, Dr. Manas (Journal of Contemporary Research in Management (JCRM), 2019)
The purpose of this study is to analyse the stock selection and the market timing ability of mutual funds managers. The data consisted of 25 mutual funds which were studied for a period of 15 years i.e. from Dec 2002 to Nov 2017. These 25 funds were selected from 17 AMCs. The study revealed that all the funds performed better than the market even with systematic risk being less than unity. Also 10 funds had risk lower than that of the market. This indicated that the returns generated could be due to the abilities of the fund manager either through stock selection or through market timing or through both. The analysis showed that all the fund managers of this 25 funds showcased stock selection ability while preparing their portfolio but had weaker market timing ability.